The Status and Prospects for Agriculture in the United Arab Emirates (UAE) and their Potential to Contribute to Food Security - Saif Al Qaydi, (Journal of Basic & Applied Sciences, 2016)
This paper focuses on the status and prospects for food production in the United Arab Emirates (UAE) and the government’s role in sourcing food to feed its people. Food security is an international issue even for those countries that have fertile soil, adequate water, and a skilled farm labor force. This is evident in the UAE, with its harsh environment, limited water resources, and infertile soil. In recent years, and as a result of the mega-development in its infrastructure and its economic activities, the UAE received more than eight million people from more than 200 ethnicities worldwide. They have not only been seeking better jobs and better life, but also with the intention to settle permanently. Their growth in the UAE population alerted the government to look for alternatives to increase food supplies other than from imports. Focusing on its local farms, and exploring the suitable new farming techniques, will bring more prosperity to the farming sector in the UAE.